Research Review: The role of diet in the treatment of attention‐deficit/hyperactivity disorder – an appraisal of the evidence on efficacy and recommendations on the design of future studies. (19th February 2014) - Stevenson, Jim; Buitelaar, Jan; Cortese, Samuele; Ferrin, Maite; Konofal, Eric; Lecendreux, Michel; Simonoff, Emily; Wong, Ian C. K.; Sonuga‐Barke, Edmund; ,
<x xml:space="preserve">Abstract</x> Background The efficacy of three dietary treatments for ADHD has been repeatedly tested in randomized controlled trials (RCTs). These interventions are restricted elimination diets (RED), artificial food colour elimination (AFCE) and supplementation with free fatty acids (SFFA). There have been three systematic reviews and associated meta‐analyses of the RCTs for each of these treatments. Scope The aim of this review is to critically appraise the studies on the dietary treatments of ADHD, to compare the various meta‐analyses of their efficacy that have been published and to identify where the design of such RCTs could be improved and where further investigations are needed. Findings The meta‐analyses differ in the inclusion and exclusion criteria applied to potentially eligible studies. The range of average effect sizes in standard deviation units is RED (0.29–1.2), AFCE (0.18–0.42) and SFFA (0.17–0.31). The methodology of many of the trials on which the meta‐analyses are based is weak. Conclusions Nevertheless, there is evidence from well‐conducted studies for a small effect of SFFA. Restricted elimination diets may be beneficial, but large‐scale studies are needed on unselected children, using blind assessment and including assessment of long‐term outcome. Artificial food colour elimination is a potentially valuable treatment but its effect size remains uncertain, as does the type of child for whom it is likely to be efficacious. There are additional dietary supplements that have been used with children with ADHD. A systematic search identified 11 RCTs that investigated the effects of these food supplements. Despite positive results for some individual trials, more studies are required before conclusions can be reached on the value in reducing ADHD symptoms of any of these additional supplements.